The Effect of Problem Based Learning Models and Auditory Learning Styles on Internship Learning Outcomes in Elementary Schools - Safril Haskin; Unik Ambar Wati; Fery Muhamad Firdaus; Ariefa Efianingrum; Diana Peggy Putinella (Universitas Pendidikan Ganesha, 2024)
Education in Indonesia faces the challenge of improving student learning outcomes through appropriate learning models and effective content delivery. This study aims to analyze the influence of Problem-Based Learning (PBL) and auditory learning styles on the critical thinking skills of elementary school students. The study employed a quantitative approach using a pre-experimental (non-design) method. Data were collected through multiple-choice tests to assess learning outcomes and questionnaires to identify students' auditory learning preferences. The sample consisted of 28 fifth-grade students. The findings revealed a significant impact of the PBL model on students with auditory learning styles in enhancing critical thinking skills. Hypothesis testing showed a probability value of 0.000 > α = 0.05, indicating a significant relationship between the learning model and student outcomes. The integration of PBL tailored to students' learning styles can effectively improve their conceptual understanding and critical thinking skills. The study concludes that implementing a problem-based learning model combined with an auditory learning style positively influences students' learning outcomes in civic education, particularly in developing critical thinking abilities in elementary school students.